PENERAPAN METODE SDLC UNTUK PERANCANGAN APLIKASI E-RENTAL MOBIL BERBASIS ANDROID PADA PT RAJAWALI PANCA UTAMA - Muhammad Ali Machrus; Muryan Awaludin (STIKOM CKI, 2016)
The techonology is nowdays growing rapidly which developing all smart features and spesifications inside is in your hand as a phone celluar as communication-life mobility. Through sending, controlling and processing file or data in which by using mobile application on phone celluar availability. Also it is supporting by system operation which flourish now is called android. Car Rent is one of the way solution through traffic jams and air pollution if it is all full on seats. For convenience in service, it’s a system operation needed. In developing a system requires modeling concepts with supporting tool named flowchart and UML, to give design on the line of the information system. In Order for the development of directional system and raise the goal are required a system development method is SDLC method with waterfall approach. Once the system is made complete and running propely can be tested by black box method that is the test input on the application to be processed according to functional needs.